2009
DOI: 10.1080/00365590903092889
|View full text |Cite
|
Sign up to set email alerts
|

Intraurethral prostate injections with mepivacaine epinephrine: Effects on patient comfort, treatment time and energy consumption during high-energy transurethral microwave thermotherapy

Abstract: Intraprostatic injections with mepivacaine epinephrine distributed by the Schelin catheter reduce the number of patients needing intravenous analgesics during PLFT, as well as the treatment time and energy consumption during treatment. Besides improved patient comfort, intraprostatic and periprostatic injections condense the treatment time without side-effects, making PLFT less cumbersome for most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is reasonable to assume that a larger prostate needs more energy delivered in order to achieve the same percentage of volume reduction, compared to a smaller prostate. In the study by Knutson et al the addition of MA when using PLFT/ CoreTherm also confirmed reduced treatment time and energy delivery [14].…”
Section: Discussionmentioning
confidence: 80%
“…It is reasonable to assume that a larger prostate needs more energy delivered in order to achieve the same percentage of volume reduction, compared to a smaller prostate. In the study by Knutson et al the addition of MA when using PLFT/ CoreTherm also confirmed reduced treatment time and energy delivery [14].…”
Section: Discussionmentioning
confidence: 80%
“…Reducing intraprostatic blood flow during surgical procedures has been addressed previously. For example, intraprostatic injections of mepivacaine and adrenaline (MA) immediately prior to transurethral microwave thermotherapy (TUMT) have been shown to significantly decrease blood flow during treatment, considerably shortening treatment time as well as energy consumption [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%